2021
DOI: 10.1371/journal.ppat.1009460
|View full text |Cite
|
Sign up to set email alerts
|

Functional regulation of the structure-specific endonuclease FEN1 by the human cytomegalovirus protein IE1 suggests a role for the re-initiation of stalled viral replication forks

Abstract: Flap endonuclease 1 (FEN1) is a member of the family of structure-specific endonucleases implicated in regulation of DNA damage response and DNA replication. So far, knowledge on the role of FEN1 during viral infections is limited. Previous publications indicated that poxviruses encode a conserved protein that acts in a manner similar to FEN1 to stimulate homologous recombination, double-strand break (DSB) repair and full-size genome formation. Only recently, cellular FEN1 has been identified as a key componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…To address this issue, the effect of hIE1_rH mutants on further cellular proteins was examined. Schilling et al showed that IE1 interacts with human flap endonuclease 1 (hFEN1), stabilising the protein to raise its activity in a pro-viral manner [ 18 ]. First, the interaction of rIE1 and IE1_rH mutants with hFEN1 aa 176-380 was analyzed by NanoBRET measurements ( Figure 5 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To address this issue, the effect of hIE1_rH mutants on further cellular proteins was examined. Schilling et al showed that IE1 interacts with human flap endonuclease 1 (hFEN1), stabilising the protein to raise its activity in a pro-viral manner [ 18 ]. First, the interaction of rIE1 and IE1_rH mutants with hFEN1 aa 176-380 was analyzed by NanoBRET measurements ( Figure 5 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to PML, hFEN1 could recently be identified as a binding partner of hIE1 that is hijacked for promoting viral replication [ 18 ]. NanoBRET analyses and cycloheximide stabilization assays revealed that rIE1 is neither able to interact with hFEN1 176-380 nor does it mediate hFEN1 protein stabilization ( Figure 5 A, bar 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations